Impulsivity and smoking relapse - Neal Doran; Bonnie Spring; Dennis E. McChargue; Michele L. Pergadia; Malia Richmond (2004)
Previous research has shown that elevated trait-impulsivity heightens the risk for initiating tobacco use and indicates that nicotine may be disproportionately rewarding for more impulsive persons. However, the influence of impulsivity on the ability to maintain nicotine abstinence has not been studied. The present study tested the hypothesis that a higher level of trait-impulsivity would predict a more rapid relapse to smoking following 48 hr of nicotine abstinence. Participants were euthymic, regular smokers (N=45), with a history of at least one major depressive episode, who participated in a paid smoking cessation study with biological challenge (tryptophan depletion). Treatment involved a 1-day skills training workshop followed by 48 hr of bioverified abstinence and weekly follow-up for 1 month. Regression analyses indicated that elevated impulsivity predicted shorter time to relapse following the workshop after controlling for treatment condition, baseline nicotine dependence, and age (β=-.39, R2 change=.147, p=.011). Greater impulsivity predicted more rapid relapse to smoking, which mediational analyses indicated could not be explained by positive affect, negative affect, or craving. Findings suggest a need to identify alternative mechanisms to explain impulsive smokers' increased difficulty in maintaining abstinence and to develop targeted treatments that address the special needs of smokers high in impulsivity.